2001
DOI: 10.1046/j.1365-2141.2001.02721.x
|View full text |Cite
|
Sign up to set email alerts
|

Greater inhibition of platelet procoagulant activity by antibody‐derived glycoprotein IIb–IIIa inhibitors than by peptide and peptidomimetic inhibitors

Abstract: Summary. Antibody-derived GPIIb±IIIa antagonists, such as the c7E3 Fab fragment abciximab, have been shown to inhibit platelet procoagulant activity as well as platelet aggregation. Whether low-molecular-weight peptide-derived and peptidomimetic antagonists also inhibit platelet procoagulant activity in a similar manner has not been fully investigated. We compared the effects of the antibodyderived antagonists c7E3 Fab and m10E5 IgG, the peptidederived antagonists eptifibatide, MK-852 and RGDS, and the peptido… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
3
6
1
Order By: Relevance
“…However, the measurements mostly concerned initial Ca 2+ rises, while in our hands only late Ca 2+ signals appear to be affected. Interestingly, one study does describe long-term inhibition of collagen/thrombin-induced Ca 2+ responses with abciximab but not with other integrin blockers specifically under conditions of stirring [23]. This contrasts with the present findings where appropriate concentrations of different integrin blockers all had similar effects.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…However, the measurements mostly concerned initial Ca 2+ rises, while in our hands only late Ca 2+ signals appear to be affected. Interestingly, one study does describe long-term inhibition of collagen/thrombin-induced Ca 2+ responses with abciximab but not with other integrin blockers specifically under conditions of stirring [23]. This contrasts with the present findings where appropriate concentrations of different integrin blockers all had similar effects.…”
Section: Discussioncontrasting
confidence: 99%
“…Several groups reported that integrin blockers were unable to change platelet Ca 2+ responses to collagen and/or thrombin [22, 23, 39]. However, the measurements mostly concerned initial Ca 2+ rises, while in our hands only late Ca 2+ signals appear to be affected.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…This is in accordance with earlier reports about an increased procoagulant activity in platelets stimulated with collagen and thrombin in the presence of MK-852, but not with thrombin as single stimulus [20].…”
Section: Discussionsupporting
confidence: 94%